Integrasi Teknologi Informasi Dan Komunikasi Dalam Pembelajaran PAI Di SDN Jatisari 05 Kedungreja Cilacap - Solehudin, Much; Yahya, Amri (Universitas Hamzanwadi, 2026)
Information and Computer Technology plays a vital role in supporting effective and efficient learning processes, particularly in the context of Islamic Religious Education, which requires a relevant approach to current developments. This study aimed to examine the integration of Information and Communication Technology (ICT) in the form of digital modules in Islamic Religious Education learning at Jatisari 05 Public Elementary School, Kedungreja, Cilacap. The integration of ICT in the form of digital modules in learning is expected to enrich teaching methods, increase student motivation, and facilitate broader access to information. The purpose of this study was to analyze the use of ICT for students in understanding Islamic Religious Education material at Jatisari 05 Public Elementary School, Kedungreja, Cilacap. This research method used a mixed method that combines quantitative and qualitative forms. Data were collected through observation, interviews, and questionnaires. Quantitative data were analyzed using an experimental design approach with the help of linear regression to test the impact of ICT use on students' understanding of Islamic Religious Education (PAI) material at SDN Jatisari 05 Kedungreja Cilacap, while qualitative data were analyzed using a descriptive analytical approach. The results of this study indicate that the integration of ICT in the form of digital modules in PAI learning can improve student understanding, strengthen learning motivation, and provide a more interactive and enjoyable learning experience. This digital module is suitable for use as an alternative PAI learning medium, with the note that technical improvements and teacher mentoring are still considered to maximize its benefits. In addition, further support is needed from the school and the government in terms of providing infrastructure and improving teacher competency in the IT field.